Implementasi Business Intelligence dalam Meningkatkan Pembuatan Dashboard dailytracker pada PT.XYZ - Ricky Rivandy A’oetpah; Binastya Anggara Sekti (Ikatan Ahli Informatika Indonesia, 2024)
Business intelligence (BI) is a technology infrastructure that analyzes data and generates reports to help managers make decisions. PT XYZ is a company engaged in insurance, which has many employees, especially in the IT and Operations divisions. Problems arise when a lot of employee daily work report data is not decomposed and cannot be analyzed by managers to make a decision. The purpose of this research is to optimize employee daily work report data with business intelligence methods in data visualization so that it can be easily analyzed and can be used as decision-making material for managers. The methods used in the research include analyzing user needs, designing business intelligence systems, implementing business intelligence systems, and testing as well as conducting qualitative methods in the form of interviews as user satisfaction surveys. The results of the application of business intelligence on the dailytracker dashboard at PT XYZ are feasible to use according to employees and managers. And the managers also gave a good response to the strategy implemented which is very informative in displaying data and can assist in analyzing data to make decisions within the company.